Analysis of economic efficiency of the use of irrigated land in agriculture and factors on them - SAFOEVNA, SHOXUJAEVA ZEBO; JURAEVNA, MAMANAZAROVA NASIBA (The journal of contemporary issues in business and government, 2021)
It is known that in recent years the water shortage in agriculture of our country has been growing sharply. Increasing the volume of agricultural production through the efficient and rational use of natural and land and water resources is a topical issue today. This article analyzes the economic efficiency of the use of irrigated land in the agricultural sector of the Kashkadarya region and the factors affecting it, and also elaborates proposals and recommendations.